Hebei women's normal education pioneers : one century's fragrant trace of wisdom - Dai, Jianbing; Wang, Yongyan (Cambridge Scholars Publishing, 2019)
This book taps into the best elements of Chinese traditional culture to show respect to the pioneers of Hebei women's education and to provide references to today's education reform and development. It contains six chapters, describing the basic requirements for Chinese women of the Feudal Period, the development of women's normal education, prominent educators in Home Economics, and the outstanding alumnae of Hebei Normal University. The book allows insights into the educational, social, cultural, economic and political movements from ancient China to the late Qing dynasty, the Republic of Ch.